Ocimum sanctum – A Herb for Chronic Diseases: Diabetes and Cancer - Kumar , Ajay; Poddar , Chandan Kumar (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
The predominant cause of global morbidity and mortality is lifestyle-related chronic diseases viz. Diabetes and cancer, which can be addressed through Ayurveda with its focus on healthy lifestyle practices and regular consumption of adaptogenic herbs. Of all the herbs used within Ayurveda, tulsi (Ocimum sanctum Linn) is preeminent, and scientific research is now confirming its beneficial effects. There is mounting evidence that tulsi can address the minimize glucose levels in diabetic patients and stop the proliferation as well as metastasis in cancer patients through a best combination phytochemical ingredient. Tulsi has been found to protect organs and tissues against severe diabetic complications. Tulsi has also been shown to counter metabolic stress through normalization of blood glucose. The use of tulsi in daily rituals is a testament to Ayurvedic wisdom and provides an example of ancient knowledge offering solutions to modern problems.